Exploring the relationship between academic self-concept and academic success in king Faisal university students - Gashlan, Baraa Mohammed M (International Journal of Innovative Research and Scientific Studies, 2025)
Academic self-concept plays a pivotal role in shaping students’ academic motivation, engagement, and performance. This study investigated the relationship between academic self-concept and academic success among students at King Faisal University in Saudi Arabia. A cross-sectional survey was conducted with 336 undergraduate and postgraduate students using a structured Arabic-translated questionnaire consisting of socio-demographic questions, the Academic Self-Concept Scale (40 items), and the Academic Success Scale (26 items). Descriptive and inferential statistics, including t-tests, ANOVA, and Pearson correlation, were performed using SPSS. The overall mean academic self-concept score was 3.06 (SD = 0.38), indicating a generally positive self-view. Significant differences in self-concept were observed based on gender (p = 0.013), age (p = 0.032), academic level (p = 0.044), GPA (p = 0.004), and discipline (p = 0.022). Academic self-concept showed a strong positive correlation with the domain “Teaching Environment and Contribution of Others” (r = 0.50, p = .001) and with “Impact of Students’ Individual Characteristics” (r = 0.48, p = .001). These results underscore the influence of both individual and contextual factors on students' academic confidence and outcomes. Educational interventions that nurture self-concept may enhance academic success. Longitudinal studies are recommended to further explore causal relationships.